Effectiveness of RTM Sabah's radio advertisement: a client's perspective / Cindy Florence Edward A. - Edward A., Cindy Florence (2013)
RTM is a renowned name in the broadcasting industry as they were the first to be established in the country. RTM has been in Sabah since 1939 that was initiated by a Telecom Engineer, Mr. Bradley. Today, Malay broadcast can be heard over Sabah FM while English, Chinese and the other four native languages can be tuned from Sabah VFM as they air the radio program from their newly located building of KPKK in Jalan Lintas Kepayan. One of the departments in RTM Sabah is the PPKS who is involved in managing the advertisement together with the help of the appointed private agency, UA. Through the PPKS department, a research was held to study the Effectiveness of RTM Sabah's Radio Advertisement: A Client's Perspective that has four objectives meant as a guideline to assess the client's perception towards the overall process of airing an advertisement. There were 124 respondents altogether who joined this research from all the five regions under the care of R TM Sabah namely; Kota Kinabalu, Tawau, Sandakan, Keningau and Labuan. As the questionnaires gathered, analyses have been run to test the reliability and correlations of the questionnaire and tabulations. Reliability statistics for this research showed Cronbach's Alpha with 0.719 which translated as a satisfactory level. The correlations significant for the cross-tabulation meant to answer the research objectives resulted fairly in between ±0.4 to ±0.7 which are considerably strong relationship. Respondents who answered the questionnaire also managed to provide some suggestion for PPKS such as to create more attractive deal package for their clients and to extend advertising period as a solution to keep clients in a longer business relationship with RTM Sabah. The expert's view on this matter is to go along with the managerial decision to be in-line with RTM's mission and vision as a whole.